2006
DOI: 10.1007/s00439-006-0153-x
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide scan in Ashkenazi Jewish families demonstrates evidence of linkage of ocular refraction to a QTL on chromosome 1p36

Abstract: The development of refractive error is mediated by both environmental and genetic factors. We performed regression-based quantitative trait locus (QTL) linkage analysis on Ashkenazi Jewish families to identify regions in the genome responsible for ocular refraction. We measured refractive error on individuals in 49 multi-generational American families of Ashkenazi Jewish descent. The average family size was 11.1 individuals and was composed of 2.7 generations. Recruitment criteria specified that each family co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
62
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 49 publications
4
62
1
Order By: Relevance
“…1,2,3 The specific genetic polymorphisms or environmental risk factors responsible remain largely unknown. Though earlier studies showed near work particularly reading, to be a significant environmental factor that may lead to myopia.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,3 The specific genetic polymorphisms or environmental risk factors responsible remain largely unknown. Though earlier studies showed near work particularly reading, to be a significant environmental factor that may lead to myopia.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable number of recognized loci, no disease genes, either for Xchromosomal recessive ('MYP1' OMIM 310460, MYP13 OMIM 300613) (15)(16)(17) or autosomal dominant disease phenotypes (MYP2 OMIM 160700, MYP3 OMIM 603221, MYP4 OMIM 608367, MYP5 OMIM 608474, MYP11 OMIM 609994, MYP12 OMIM 609994, and myopia locating to chromosome 10q21.1) (18)(19)(20)(21)(22)(23)(24) have been identified. This also holds true for the genes involved in common myopia where six independent loci have been determined in the recent past (MYP6 OMIM 608908, MYP7 OMIM 609256, MYP8 OMIM 609257, MYP9 OMIM 609258, MYP10 OMIM 609259, and MYP14 OMIM 610320) (25)(26)(27).…”
Section: Introductionmentioning
confidence: 88%
“…To our knowledge, there have only been two linkage studies that have considered ocular refraction as a quantitative trait. 39,40 The first, published by Hammond et al, 39 identified myopia susceptibility loci on 11p13 (MYP7), 3q26 (MYP8), 4q12 (MYP9), and 8p23 (MYP10) using spherical equivalent as the phenotype. Theirs is the only linkage study into myopia that has used a twin-based cohort.…”
mentioning
confidence: 99%
“…17 The second study assessing ocular refraction as a quantitative trait identified a single susceptibility locus on 1p36 in Ashkenazi Jewish families. 40 To date, there have been no linkage studies assessing ocular biometric measurements such as ocular axial length, corneal curvature, and anterior chamber depth as underlying quantitative traits for ocular refraction.We have reported heritability of ocular refraction and ocular biometric measurements in a twin-based population. 9 The twins used for this heritability study were recruited as part of the Genes in Myopia (GEM) Twin Study.…”
mentioning
confidence: 99%